EVALUATION OF TOOL WEAR AND BURR FORMATION IN MICRO-DRILLING TITANIUM TI-6AL-7NB - Mohd Affifudin, Abdul Patar; Mohd Azlan, Suhaimi; Jinnie Gan, Jing Nee; Safian, Sharif; Muhammad, Yanis; Amrifan Saladi, Mohruni; Kejia, Zhuang (JURNAL TEKNOLOGI, 2026)
Titanium, renowned for its corrosion resistance and strength, is extensively utilized across various industries. Titanium alloy Ti-6Al-7Nb, also known as Titanium 367, is particularly favoured for total hip prostheses, especially in femoral stems, due to its excellent corrosion resistance and biocompatibility. This alloy is also employed in knee replacements, dental procedures, and maxillofacial applications for screws, plates, and implants, highlighting its versatility in the medical field. However, machining titanium alloys presents significant challenges due to their poor machinability. This study investigates the impact of selected cutting parameters, including spindle speed and feed rate, as manipulated variables while maintaining point angle as a constant variable on micro-drilling using 2mm uncoated carbide drills. The experimental analysis identifies three phases of tool wear: initial, steady, and severe. The results indicate a linear increase in flank wear with higher spindle speeds and feed rates. Burr height is notably higher at increased spindle speeds and feed rates. Burr height is primarily influenced by feed rate, which determines chip load and material removal per revolution. The individual effects of these parameters on burr formation are significant. At the highest spindle speed, a crown burr with a drill cap is formed due to intense friction and heat, which softens the material and facilitates cap formation over the exit hole. This study validates a predictive model for burr height and tool wear, providing a foundation for parameter optimization in real-world applications.